Introduction of a Multimodal Pain Rehabilitation Intervention in Primary Care: A Pilot Study - Katarina Eklund; Britt-Marie Stålnacke; Annica Sundberg; Fredrik Eklund; Mikael Eklund (Journal of Rehabilitation Medicine - Clinical Communications, 2023)
Objective: To evaluate patient-reported outcome measures in patients with chronic musculoskeletal pain 1 year after participation in a case manager-led multimodal rehabilitation intervention in a Finnish primary care centre. Changes in healthcare utilization (HCU) were also explored. Methods: A prospective pilot study with 36 participants. The intervention consisted of screening, multidisciplinary team assessment, a rehabilitation plan and case manager follow-up. Data were collected through questionnaires filled in after the team assessment and 1 year later. HCU data 1 year before and 1 year after team assessment were compared. Results: At follow-up, satisfaction with vocational situation, self-reported work ability and health-related quality of life (HRQoL) had improved and pain intensity had diminished significantly for all participants. The participants who reduced their HCU improved their activity level and HRQoL. Early intervention by a psychologist and mental health nurse was distinctive for the participants who reduced HCU at follow-up. Conclusion: The findings demonstrate the importance of early biopsychosocial management of patients with chronic pain in primary care. Identification of psychological risk factors at an early stage may lead to better psychosocial wellbeing, improve coping strategy and reduce HCU. A case manager may free up other resources and thereby contribute to cost savings.